Simple Shapes Elicit Different Emotional Responses in Children with Autism Spectrum Disorder and Neurotypical Children and Adults - Belin, Laurine; Henry, Laurence; Destays, Mélanie; Hausberger, Martine; Grandgeorge, Marine (Frontiers in Psychology, 2017)
According to the literature, simple shapes induce emotional responses. Current evaluations suggest that humans consider angular shapes as “bad” and curvilinear forms as “good”, but no behavioral data are available to support this hypothesis. Atypical development, such as autism spectrum disorder (ASD), could modify humans’ perception of visual stimuli, and thereby their emotional effect. This study assessed the effects of simple stimuli (i.e. jagged edges, disc, star, spiral, eye-like shapes and head character) on the emotional responses of different groups of humans. First, we assessed the effects of a looming movement on neurotypical adults’ emotional responses. Second, we assessed the effects of atypical development on emotional responses by comparing the reactions of neurotypical children and of children with ASD. We used different methodological approaches: self-evaluation through questionnaires and direct observation of participants’ behavior. We found that 1) neurotypical adults tended to perceive looming stimuli negatively as they associated more negative feelings with them although few behavioral responses could be evidenced and 2) the emotional responses of neurotypical children and of children with ASD differed significantly. Neurotypical children perceived the spiral stimulus positively, i.e. a curvilinear shape, whereas children with ASD perceived the jagged edges stimulus positively, i.e. an angular shape. Although neurotypical children and children with ASD presented some behavioral responses in common, children with ASD smiled and vocalized more than did neurotypical children during stimuli presentations. We discuss our results in relation to the literature on humans’ perception of simple shapes and we stress the importance of studying behavioral components for visual cognition research.